EFEKTIVITAS KERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN SUKOHARJO - Wahyu Bhudianto, M Rizki Saputra, Liliek Winarni & (Transformasi, 2016)
Research objective description effectiveness employee on education committee inSukoharjo District. The indicators of measurement is skill adjust oneself of employee, workperformance, and job satisfaction. The kind of the research to use descriptive qualitative. Thekind of the data to use Interview and Observation and also legislation of law about problemstatement that investigated.From this research was doing, the researcher to conclude that fordescribing the effectiveness of employee on education committee in Sukoharjo District,dimension ability of adjust oneself such as the join of employee on education committee alreadythat enough and rare that happens misconception in employee on education committee inSukoharjo District for communication itself. The employer always the communication links thatenough, without any communication the employer will be experienced problems in a work.Dimension ability consist of skills, background of study that enough with working that give byemployee, to discipline and responsibility of the employer on working in ways better. Dimensionof work satisfaction such as, Organization and honors or financial .In research on educationcommittee that enough have been the employer can be maximizing of the effectiveness workingthem in education committee in Sukoharjo District.The conclusion of the effectiveness of polityemployee in education committee located to all the employer that achievement for the purpose ofgeneral organization and also intansi must be maximum in working, such as that explaining todescribing that above .And visions h to created will be achievement with satisfy.Keywords: effectiveness of the employee ,adaptability ,workability.